Sensorineural Hearing Loss as the Prominent Symptom in Meningeal Carcinomatosis. - Xiaoqin Huang; Yu Jia; Lidong Jiao (Current Oncology, 2021)
Sensorineural hearing loss (SNHL) has been reported rarely in patients with meningeal carcinomatosis (MC). We summarized the clinical data of eight MC patients with SNHL and 35 patients reported from publications. In the eight patients with SNHL, the medium onset age was 48 (range from 37 to 66) years and six (75%) were male. Seven (87.5%) suffered from headaches as the initial symptom, and they experienced SNHL during the first two months after the occurrence of headaches (0.5 to 2 months, average 1.5 months). The audiogram configuration was flat in three patients (37.5%) and showed total deafness in five patients (62.5%). The damage of cranial nerves VI (abducens) was observed in six patients (75%), and four patients (50%) had cranial nerves VII (facial) injury during the disease course. The percentage of damage of cranial nerves was higher than the patients without SNHL (VIth, 75.0% vs. 13.3%, p = 0.002 and VIIth 50.0% vs. 6.7%, p = 0.012). Four (50%) patients suffered from lung adenocarcinoma as primary tumor, two (25%) experienced stomach adenocarcinoma, one had colon cancer, and one patient was unknown. The symptom of SNHL improved after individualized therapy in four patients (focal radiotherapy and chemotherapy for three patients and whole brain radiotherapy for one patient), but all passed away from 2 to 11 months after diagnosis. Total deafness and flat hearing loss in audiogram were the common types of SNHL resulting from MC. MC patients with SNHL were more likely to suffer from the damage of other cranial nerves, especially to cranial nerves VI and VII. Treatment might improve SNHL, but not improve the case fatality rate.